Collagen use in splenic rupture - Mesa, Guillermo; de Pena, Mario; Acosta y Lara, Armando; Doassans, Carlos; Torres, Marcos; Cotic, Graciela; Kwasina, Tomislav (Cirugía del Uruguay, 1983)
An experimental work in a serie of 20 mices to whom a partial resección of spleen was practiced, is analized. To 15 of they, a collagen graft was applicated. Phisiopatological b asis, necropsic founds, results and conclusions are analized.